2021
DOI: 10.1183/13993003.04107-2020
|View full text |Cite
|
Sign up to set email alerts
|

Asthma prescribing according to Arg16Gly beta-2 genotype: a randomised trial in adolescents

Abstract: IntroductionThe A allele of rs1042713 (Arg16 amino acid) in the beta-2 (β2) adrenoreceptor is associated with poor response to long-acting β2-agonist (LABA) in young people with asthma. Our aim was to assess whether the prescribing of second line controller with LABA or a leukotriene receptor antagonist (LTRA) according to Arg16Gly genotype would result in improvements in pediatric asthma-related quality of life questionnaire (PAQLQ).MethodsWe performed a pragmatic randomised controlled trial (RCT) via a prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…We acknowledge that theophylline has a narrower therapeutic interval compared to LABAs, yet importantly the inhaled route of administration of LABAs is prone to incorrect use and non-adherence [4]. We wonder if patients were assessed for inhaler adherence and whether inhaler technique was checked and patients trained, as these factors may have explained the heterogeneity in response to treatment and possibly, as reported by the authors, a lower than expected effect observed for personalised medicine in their study [1].…”
Section: When Biology Meets Behaviour: Can Medication Adherence Mask ...mentioning
confidence: 89%
See 2 more Smart Citations
“…We acknowledge that theophylline has a narrower therapeutic interval compared to LABAs, yet importantly the inhaled route of administration of LABAs is prone to incorrect use and non-adherence [4]. We wonder if patients were assessed for inhaler adherence and whether inhaler technique was checked and patients trained, as these factors may have explained the heterogeneity in response to treatment and possibly, as reported by the authors, a lower than expected effect observed for personalised medicine in their study [1].…”
Section: When Biology Meets Behaviour: Can Medication Adherence Mask ...mentioning
confidence: 89%
“…We read the study of RUFFLES et al [1] with great interest. The authors undertook one of the first randomised controlled trials (RCTs) assessing the potential benefit of personalised prescription of bronchodilators according to Arg16Gly beta-2 genotype in adolescent patients with asthma.…”
Section: When Biology Meets Behaviour: Can Medication Adherence Mask ...mentioning
confidence: 99%
See 1 more Smart Citation
“…This meta-GWAS contributes to knowledge of pharmacogenetic markers that can determine whether children experience exacerbations despite LABA use, potentially leading to further understanding of which patients would benefit from LABA treatment. Further investigation in future studies including data in children with exacerbations despite LABA use (such as the PACT trial 64 and the PUFFIN trial 65 once these are genome-wide genotyped) could potentially lead to more concise meta-GWAS results.…”
Section: Discussionmentioning
confidence: 99%
“…There may be ethnic differences in response to LABA, making it more complex to discover SNPs associated with exacerbations despite LABA use. Accordingly, the wide confidence intervals demonstrated for I 2 potentially indicate the presence of a reasonable amount of heterogeneity, which is presumably due to the limited number of studies included in the meta-analyses 63. Moreover, previous analysis of SAGE and GALA II genotyped with an array optimized for those admixed populations has revealed previously unknown SNPs for asthma exacerbations 55 despite ICS use.…”
mentioning
confidence: 99%